Why Senescent Cells Are Resistant to Apoptosis: An Insight for Senolytic Development - Hu, Li; Li, Huiqin; Zi, Meiting; Li, Wen; Liu, Jing; Yang, Yang; Zhou, Daohong; Kong, Qing-Peng; Zhang, Yunxia; He, Yonghan (Frontiers in Cell and Developmental Biology, 2022)
Cellular senescence is a process that leads to a state of irreversible cell growth arrest induced by a variety of intrinsic and extrinsic stresses. Senescent cells (SnCs) accumulate with age and have been implicated in various age-related diseases in part via expressing the senescence-associated secretory phenotype (SASP). Elimination of SnCs has the potential to delay aging, treat age-related diseases and extend healthspan. However, once cells becoming senescent, they are more resistant to apoptotic stimuli. Senolytics can selectively eliminate SnCs by targeting the SnC anti-apoptotic pathways (SCAPs). They have been developed as a novel pharmacological strategy to treat various age-related diseases. However, the heterogeneity of the SnCs indicates that SnCs depend on different proteins or pathways for their survival. Thus, a better understanding of the underlying mechanisms for apoptotic resistance of SnCs will provide new molecular targets for the development of cell-specific or broad-spectrum therapeutics to clear SnCs. In this review, we discussed the latest research progresses and challenge in senolytic development, described the significance of regulation of senescence and apoptosis in aging, and systematically summarized the SCAPs involved in the apoptotic resistance in SnCs.